PKM PENGOLAHAN TEH SARANG SEMUT KERJASAMA KELOMPOK TANI HUTAN (KTH) WENDY, KPHP UNIT V SORONG SELATAN & MAHASISWA PKL KEHUTANAN UM SORONG DI KAMPUNG WENDY KABUPATEN SORONG SELATAN - Azis Maruapey; Lona H. Nanlohy; Fajrianto Saen; Sanny Hahury; Rajab Lestaluhu (Yayasan Education and Social Center, 2023)
This Community Service Activity Program (PkM) aims to make the community in the utilization and processing of ant plants into tea bags for ant nests. In this activity, the community was provided with information on how to process ant nests into tea bags made from ant nests in order to add to the economic value of these commodities. At the end of the activities carried out with the Forest Farmers Group (KTH) Wendy, the KPHP Unit V South Sorong, UM Sorong Field Work Practice (PKL) students, where KTH was guided from selecting raw materials, treating raw materials to processing and product packaging processes. The methods used in this community service activity are lectures and demonstrations with the aim of creating the community's ability to produce tea bags from ant nests. This activity was held at the KPHP Unit V Office in South Sorong which was attended by around KTH Wendi who came from Kampung Wendy, with the results of this activity going well with the results showing that there had been an increase in KTH's understanding and skills in carrying out the production process, as well as community adaptation to equipment which is used to support the production process starting from preparation, processing and packaging